2021
DOI: 10.1111/cod.13873
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing of budesonide in Italy: The SIDAPA baseline series experience, 2018–2019

Abstract: Background Budesonide was included in the European Baseline Series in 2000 as the most suitable marker forcorticosteroid hypersensitivity. In the last two decades, a decreasing trend of budesonide allergy has been observed. Objectives To estimate the prevalence of positive patch test reactions to budesonide in a large, Italian patch test population, characterizing patients according to MOAHLFA index and evaluating the benefit with extended readings of budesonide patch test. Methods Retrospective analysis of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
3
10
0
2
Order By: Relevance
“…A Belgium study reported an overall budesonide sensitization of 1.9% between 1990 and 2014 23 . Recently, European multicentre studies reported decreased prevalence of 0.6%–0.7%, 3,4,18 while the prevalence in our study was stable from 2006 to 2020.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…A Belgium study reported an overall budesonide sensitization of 1.9% between 1990 and 2014 23 . Recently, European multicentre studies reported decreased prevalence of 0.6%–0.7%, 3,4,18 while the prevalence in our study was stable from 2006 to 2020.…”
Section: Discussionsupporting
confidence: 49%
“…23 However, most recently, Murphy et al 28 4 Age above 40 years was an only individual risk factor for development of corticosteroid sensitization, as previously reported. 3,18 The time lived intuitively increase risk of corticosteroid skin contact, risk of chronic dermatosis and thereby cumulative dose of topical corticosteroids. The risk of inducing contact sensitization to corticosteroids is increased by cumulative exposure, simultaneous occlusion, potency of the allergen and the nature of the skin treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also underscores the importance of a late reading, as 17.0% of positive patch test results only manifested on day 7. This was especially the case for neomycin (56.5%), budesonide (44.4%), and flavine (42.9%), which is consistent with our previous study and the existing literature 2,9 …”
Section: Discussionsupporting
confidence: 92%
“…Topical corticosteroids (TCS) are used as first‐line therapy in the management of patients with AD for both acute flares and maintenance, showing promising efficacy for AD patients 31,32 . However, due to its adverse events (AEs) such as skin atrophy, striae, and allergic contact dermatitis, as well as unsatisfied efficacy in the moderate and severe forms, TCS is limited for its usage in AD patients 32–34 . With the development of topical (such as tacrolimus and sirolimus) and systematic therapy (such as dupilumab, nemolizumab, and lebrikizumab) for AD, new drugs had significantly improved the symptom of pruritus and skin lesions of AD patients, with a satisfying safety profile.…”
Section: Discussionmentioning
confidence: 99%